2020
DOI: 10.1002/ccr3.2839
|View full text |Cite
|
Sign up to set email alerts
|

Effective removal of solar lentigines by combination of pre– And post–fluorescent light energy treatment with picosecond laser treatment

Abstract: We present a novel treatment for removal of SL that is efficient and enables removal or lesions not immediately visible. Kleresca® FLE technology combined with picosecond laser treatment removes SL lesions and improves skin quality and appearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Prior studies have demonstrated the efficacy and safety of picosecond lasers in solar lentigines treatment, both alone or in combination therapy. Scarcella et al showed the success of solar lentigines removal and enhanced rejuvenation at treated areas, when using the 532‐nm picosecond laser in combination with bio‐photonic treatment 28,29 . To the best of our knowledge, ours is the first study to compare the KTP 532‐nm and alexandrite 755‐nm picosecond lasers for removing solar lentigines in darker skin types.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Prior studies have demonstrated the efficacy and safety of picosecond lasers in solar lentigines treatment, both alone or in combination therapy. Scarcella et al showed the success of solar lentigines removal and enhanced rejuvenation at treated areas, when using the 532‐nm picosecond laser in combination with bio‐photonic treatment 28,29 . To the best of our knowledge, ours is the first study to compare the KTP 532‐nm and alexandrite 755‐nm picosecond lasers for removing solar lentigines in darker skin types.…”
Section: Discussionmentioning
confidence: 84%
“…Scarcella et al showed the success of solar lentigines removal and enhanced rejuvenation at treated areas, when using the 532-nm picosecond laser in combination with bio-photonic treatment. 28,29 To the best of our knowledge, ours is the first study to compare the KTP 532-nm and alexandrite 755-nm picosecond lasers for removing solar lentigines in darker skin types. A relatively large population of 30 subjects and a total of 60 lentigines were recruited.…”
Section: Discussionmentioning
confidence: 99%
“…It is typically associated with older age and is located on body areas with high sun exposure, such as the face and hands. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Current treatments may include topicals (eg, hydroquinone, retinoids, steroids), cryotherapy, chemical peels (eg, glycolic acid, salicylic acid), or laser therapy. 5 , 12 However, many of these treatments are associated with negative side effects. Hydroquinone has been found to be effective for PIH and solar lentigines but is relatively slow to work and can cause hypersensitivity and acneiform eruptions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, FLE has been shown to significantly impact healthy [ 16 ], inflamed, and disease-affected skin tissues. The latter being well-documented in clinical trials and case studies, for acne [ 17 , 18 ], rosacea [ 19 , 20 ], acne conglobate and hidradenitis suppurativa [ 21 ], acneiforme eruption [ 22 ], senile lentigines [ 23 , 24 ], and wound healing [ 13 , 25 , 26 , 27 ]. Finally, a series of case studies investigating the effect of FLE treatment on healing of acute second-degree burns showed accelerated wound healing as well as overall improvement of tissue structure in two cases of severe HTS after burn injuries, suggesting that FLE balances wound healing at different stages of the wound healing and remodeling process [ 28 ].…”
Section: Introductionmentioning
confidence: 99%